Perceptions of patients with diabetes mellitus regarding multiprofessional assistance in the family health strategy (Revista Brasileira Multidisciplinar, 2025)
Type 2 Diabetes Mellitus (T2DM) is one of the leading causes of morbidity and mortality. Brazil has a high incidence of T2DM, ranking fifth worldwide. Primary Health Care (PHC) plays a crucial role in the management of T2DM through the Family Health Strategy (FHS) and multiprofessional teams. The aim of this study is to comprehend the perception of female users diagnosed with T2DM regarding the assistance provided by the multiprofessional team in the Family Health Strategy. This is a descriptive, qualitative study conducted in a municipality in the southeastern region of Mato Grosso, with female users diagnosed with T2DM and followed up by an FHS. Data were collected through semi-structured interviews and subjected to thematic content analysis. The ethical aspects of research with human beings were ensured. Eight women participated in the study, and two categories emerged from the interviews: “Bond and welcoming relationship between users and the multiprofessional team” and “Perception of the educational activities carried out by the multiprofessional team in disease management.” The importance of establishing bonds and the positive perception of the welcoming approach were noted. However, some users expressed dissatisfaction with communication and the lack of information about T2DM during consultations. There is a perceived need for improvements in communication between professionals and users, emphasizing the importance of health education to promote changes in lifestyle habits and better management of T2DM.
Keywords: Type 2 diabetes mellitus; Multiprofessional team; Primary health care